THE EFFECT OF EARNING PER SHARE, INVESTMENT OPPORTUNITY SET, TOTAL ASSET TURNOVER, AND COLLATERALIZABLE ASSET ON DIVIDEND POLICY (Research on Consumer Goods Industrial Sector Companies Listed on the Indonesian Stock Exchange for the 2015-2019 period) - Annisa Rizal; Dedik Nur Triyanto (UNIB Press, 2021)
Dividend policy is a company's decision to determine whether the profits earned by the company will be distributed to investors in the form of dividends or by increasing the company's retained earnings. The purpose of this research was to determine the effect of earnings per share, investment opportunities, total asset turnover, and collateralizable assets on dividend policy in consumer goods industry entities listed on the Indonesia Stock Exchange for the 2015-2019 period. The population in this research was the consumer goods industry listed on the Indonesia Stock Exchange of 52 entities in 2015-2019. The technique of determining the sample used is purposive sampling. The samples obtained are 13 companies incorporated in the consumer goods industry sectors in the Indonesia Stock Exchange for 2015-2019. Based on the analysis, the result shows that the variable total asset turnover partially has a significant positive effect on dividend policy. Collateralizable asset variable has a significant negative impact on dividend policy. In contrast, the investment opportunity variables and earnings per share don't affect dividend policy. This research can be used as a reference for stakeholders in the company to consider the total asset turnover that affects dividend policy in a company.